Micotoxinas, o que precisa saber - Alvito, Paula (2022)
Infográfico sobre micotoxinas desenvolvido no âmbito do projeto HBM4EU. HBM4EU is a joint effort of 30 countries, the European Environment Agency and the European Commission.